2005
DOI: 10.1007/s00122-005-0153-6
|View full text |Cite
|
Sign up to set email alerts
|

Leaf tip necrosis, molecular markers and β1-proteasome subunits associated with the slow rusting resistance genes Lr46/Yr29

Abstract: Resistance based on slow-rusting genes has proven to be a useful strategy to develop wheat cultivars with durable resistance to rust diseases in wheat. However this type of resistance is often difficult to incorporate into a single genetic background due to the polygenic and additive nature of the genes involved. Therefore, markers, both molecular and phenotypic, are useful tools to facilitate the use of this type of resistance in wheat breeding programs. We have used field assays to score for both leaf and ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
62
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(73 citation statements)
references
References 26 publications
3
62
0
7
Order By: Relevance
“…Obert et al (2005) tagged new slow-rusting resistance genes to leaf rust from Afghanistan landraces of wheat using AFLP, and mapped this new gene on chromosome 5BS with SSRs. Rosewarne et al (2006) identified and mapped new AFLP markers associated with the Lr46/Yr29 complex, an important gene to APR in wheat. In oat, which has the largest cereal genome, Barbosa et al (2006) tagged partial resistance to oat crown rust by using the AFLP technique.…”
Section: Discussionmentioning
confidence: 99%
“…Obert et al (2005) tagged new slow-rusting resistance genes to leaf rust from Afghanistan landraces of wheat using AFLP, and mapped this new gene on chromosome 5BS with SSRs. Rosewarne et al (2006) identified and mapped new AFLP markers associated with the Lr46/Yr29 complex, an important gene to APR in wheat. In oat, which has the largest cereal genome, Barbosa et al (2006) tagged partial resistance to oat crown rust by using the AFLP technique.…”
Section: Discussionmentioning
confidence: 99%
“…The Ltn associated with Lr34/Yr18 is quantitatively expressed and it shows a variable expression in different genetic backgrounds when tested under different environmental conditions (Messmer et al 2000;Rosewarne et al 2006). Owing to the absence of Ltn in cultivar PBW65 it can be suggested that the cultivar PBW65 does not carry the gene Lr34.…”
Section: Discussionmentioning
confidence: 99%
“…The genes conditioning race non-specific resistance are characterized by their inability to evoke a hypersensitive response, slowing of the pathogen growth, partial resistance phenotype, additive nature , optimal expression at the adult plant stage and long-term effectiveness (durability) (McIntosh et al 1995;Messmer et al 2000;Suenaga et al 2001Suenaga et al , 2003Singh et al 2004;Navabi et al 2005;Spielmeyer et al 2005;Bossolini et al 2006). Durability of resistance to leaf rust due to the gene Lr34 (Dyck 1987;McIntosh 1992;Singh 1992a, b;Singh & Rajaram 1992;Suenaga et al 2003) and Lr46 (Singh et al 1998;Martinez et al 2001;William et al 2003;Rosewarne et al 2006) has so far been reported to be associated with non-hypersensitive adult plant resistance (APR). Both these genes are also linked to stripe rust resistance (Singh 1992a, b;Singh & Rajaram 1992;Singh et al 1998;Martinez et al 2001;William et al 2003;Suenaga et al 2003;Rosewarne et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Отдельный интерес представляют гены, формирующие неспецифическую устойчивость, поскольку она обеспечивает длительный период эффективности сразу к нескольким патогенам, что делает ее предпочтительной для селекционеров и исследователей. У пшеницы подробно охарактеризованы всего четыре гена Lr34, Lr46, Lr67 и Lr27, определяющих замедленное развитие сразу нескольких заболеваний, два из которых, Lr34 и Lr67, были секвенированы (Rosewarne et al, 2006;Mago et al, 2011;Spielmeyer et al, 2013).…”
unclassified